The molecular pathophysiology of depression and the new therapeutics - Tian, Haihua; Hu, Zhenyu; Xu, Jia; Wang, Chuang (MedComm (2020), 2022)
Major depressive disorder (MDD) is a highly prevalent and disabling disorder. Despite the many hypotheses proposed to understand the molecular pathophysiology of depression, it is still unclear. Current treatments for depression are inadequate for many individuals, because of limited effectiveness, delayed efficacy (usually two weeks), and side effects. Consequently, novel drugs with increased speed of action and effectiveness are required. Ketamine has shown to have rapid, reliable, and long‐lasting antidepressant effects in treatment‐resistant MDD patients and represent a breakthrough therapy for patients with MDD; however, concerns regarding its efficacy, potential misuse, and side effects remain. In this review, we aimed to summarize molecular mechanisms and pharmacological treatments for depression. We focused on the fast antidepressant treatment and clarified the safety, tolerability, and efficacy of ketamine and its metabolites for the MDD treatment, along with a review of the potential pharmacological mechanisms, research challenges, and future clinical prospects. This review aimed to clarify the safety, tolerability, and efficacy of ketamine and its metabolites for the treatment of major depressive disorder (MDD), along with a review of potential pharmacological mechanisms, research challenges, and future clinical prospects. Many novel hubba proteins and MDD‐risk proteins were found, indicating that the current pharmacological mechanisms were just the tip of the iceberg.